Persepsi Dosen Jurusan Akuntansi Politeknik Negeri Ambon Terhadap Penggunaan Fintech QRIS - Hasmawati Hasmawati; Rendy Usmany; Fajarina Siwabessy; Aling Sadewai Tumbelaka; Mufidah Faradillah Lamasano; Mario Delfiero Hutasoit (Fakultas Ekonomi Universitas Negeri Manado, 2024)
The rapid advancement of information and communication technology in the digital era has significantly impacted various aspects of human life, including the field of accounting. Information technology has revolutionized accounting systems and organizational operations, making them more efficient and effective. One of the fastest-growing financial technologies (fintech) in Indonesia is QRIS (Quick Response Code Indonesian Standard), an electronic payment standard developed by Bank Indonesia. This study aims to examine the perceptions of Accounting lecturers at Ambon State Polytechnic regarding the use of QRIS fintech as a payment transaction tool. The data analysis process in this study involves collecting interview results, simplifying and presenting the data in descriptive verbal form, re-checking the presented data, and drawing conclusions to verify and transform the analyzed data into accurate and reliable information. The findings reveal that fintech is effective because its ease of transactions, its practicality, and the benefits it offers to users.